Multi-deal agriculture and urban revitalisation. The forest in the city - Adornato, Francesco (Przegląd Prawa Rolnego, 2025)
This article explores the multifaceted nature of agriculture, focusing particularly on urban forests and their ability to transform the relationship between cities and the countryside. After providing a historical overview of the role of forests, the article turns to the various phenomena of agriculture which were overlooked in the Italian Civil Code of 1942, but recognised by the European legislator in Article 39 of the Treaty of Rome. However, the multifunctional connotation is insufficient to encompass the contemporary complexity of new agro-forestry forms, which should be traced to the broader category of multi-crop agriculture. The roots of this category lie in the ethical, institutional, social, and economic-legal content in which the forest plays a central role. Emblematic of this are the experiences of “forests in the city,” which demonstrate further forms of pluralisation related to integration, health, and the regeneration of urban areas. In such a scenario, lawyers must not only interpret, but also innovate due to the progressive diffusion of urban agricultural activities within an irreversible legal and social context.